Dog Company : a true story of American soldiers abandoned by their high command - Hill, Roger T.; Vincent, Lynn (Center Street, 2017)
"Two decorated American war heroes survive combat in Afghanistan only to find themselves on an unfamiliar battlefield--the courtroom--in this true story by the commander of Delta Company, 1/506th a.k.a. Dog Company. The deaths of two of his men is agony for Captain Roger Hill and the agony is intensified when he realizes those responsible--12 Taliban spies--have been working right under his nose on the American base. When unreasonable military regulations demand that he free the spies within 96 hours, and Hill can't get his superior officer to respond to the deadline, he takes action to intimidate the prisoners to confess--and to protect his company from another attack. Instead of being thanked, Hill's superior brings him up on charges making this decorated officer's next battle a personal one--for his honor and for that of 1st Sergeant Tommy Scott, his second in command. Combining the camaraderie and battle action of Band of Brothers with the military courtroom drama of A Few Good Men, Roger Hill's story will leave you impassioned, inspired and forever changed"--Provided by publisher.